2011
DOI: 10.21608/jpp.2011.85637
|View full text |Cite
|
Sign up to set email alerts
|

Productivity of Some Summer Forage Crops Under Sprinkler Irrigation in Newly Reclaimed Soil Conditions.

Abstract: Two field experiments were carried out at Al-Hussein Society For Reclaiming And Cultivating land-64 km. Cairo Alexandria desert road, Giza Governorate. Egypt, during two successive summer seasons , 2006 and 2008, to study the effect of three irrigation rates (1500, 2000 and 2500 m³/ fad. per season) on yield and the water use efficiency expressed as kg dry yield/m³ of water consumed, of some sole and mixture summer forage crops, which were: sorghum (Sorghum bicolour ,L.), variety local hybrid 102, pearl millet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…On the other hand, the herbage DMY for Cowpea-82d889 (8.4 t/ha) is comparable with a reported mean value of 8.76 t/ha reported for three improved cowpea cultivars grown in Southwest Nigeria. Rizk et al (2011) studied the productivity of some summer forage crops under three irrigation rates (1500, 2000 and 2500 m³/fad./ eason) using sprinkler irrigation system in newly reclaimed soil conditions; they found that, the irrigation water rates were significance effective on the total fresh and dry yields of cowpea in both seasons. Where, in the first season, the total fresh yield was; 12.51, 16.82 and 17.64 ton/fad; respectively, by average mean 15.66 ton/fad.…”
Section: Mean Performance Of Forage Yield and Quality Of Cowpea: Forage Yield In Cowpeamentioning
confidence: 99%
“…On the other hand, the herbage DMY for Cowpea-82d889 (8.4 t/ha) is comparable with a reported mean value of 8.76 t/ha reported for three improved cowpea cultivars grown in Southwest Nigeria. Rizk et al (2011) studied the productivity of some summer forage crops under three irrigation rates (1500, 2000 and 2500 m³/fad./ eason) using sprinkler irrigation system in newly reclaimed soil conditions; they found that, the irrigation water rates were significance effective on the total fresh and dry yields of cowpea in both seasons. Where, in the first season, the total fresh yield was; 12.51, 16.82 and 17.64 ton/fad; respectively, by average mean 15.66 ton/fad.…”
Section: Mean Performance Of Forage Yield and Quality Of Cowpea: Forage Yield In Cowpeamentioning
confidence: 99%